THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP ON ORGANIZATIONAL COMMITMENT AND ORGANIZATIONAL CITIZENSHIP BEHAVIOUR (OCB) OF EMPLOYEES AT TERENGGANU’S GOVERNMENT LINKED COMPANIES (GLCS): A CONCEPTUAL FRAMEWORK - Muhammad Al Azzim Mohd Zaki; Juhaizi Mohd Yusof; Nur Aishah Awi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
This study provides a conceptual framework for understanding the impact of transformational leadership on organizational commitment and organizational citizenship behaviour (OCB) among employees in Terengganu’s Government Linked Companies (GLCs). In this context, this paper mainly aims at providing a new perspective to understand the occurrence of organizational commitment. It seeks to intrinsically enhance the employees for their discretionary behaviours to the organization’s activities. To date, only limited studies are available that consider OCB as a connection developer between transformational leadership and organizational commitment. Organizational commitment is a critical concept with multiple antecedents and implications for organizational performance, goals, employee turnover, and work satisfaction. Employees’ commitment to their jobs and organizations is determined by situational and dispositional factors, or by a combination of the two. This study examines how leaders’ influences drive employees’ OCB and its relationship with organizational commitment. The framework suggests that transformational leadership has a direct influence on organizational commitment and employeesâ€™ OCB. It is hypothesised that OCB both directly influence and mediate transformational leadership on organizational commitment.